2005
DOI: 10.1021/jo051202m
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Stabilized Phenylboranylidene Groups Having a Dimethoxytrityl Group as a Colorimetrically Detectable Protecting Group Designed forcis-1,2-Diol Functions of Ribonucleosides in the Solid-Phase Synthesis of m22,2G5ppT

Abstract: To not only improve the inherently poor stability of the phenylboranylidene group as a protecting group of the 2',3'-cis-diol function of ribonucleosides but also introduce a colorimetrically detectable function into its mother structure, various 2-[(dialkylamino)methyl]phenylboronic acid derivatives having a [(4,4'-dimethoxytrityl)oxy]methyl group were synthesized. The reaction of uridine with these substituted phenylboronic acid derivatives gave the corresponding 2',3'-O-phenylboranylideneuridine derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Several methods have been reported for preparing m 2 G and m 2 2 G derivatives but the most straightforward one used a “one‐step” reductive amination reaction to methylate the exocyclic amine directly . We attempted to combine the reductive amination with Beigelman's protecting strategy to synthesize both phosphoramidites 7 a and 7 b at the same time.…”
Section: Figurementioning
confidence: 99%
“…Several methods have been reported for preparing m 2 G and m 2 2 G derivatives but the most straightforward one used a “one‐step” reductive amination reaction to methylate the exocyclic amine directly . We attempted to combine the reductive amination with Beigelman's protecting strategy to synthesize both phosphoramidites 7 a and 7 b at the same time.…”
Section: Figurementioning
confidence: 99%
“…Since the pioneering work of Yurkevich et al, 80 the use of boronic acids as 2 0 ,3 0 -dihydroxyl protecting groups for ribonucleosides has been widely developed. [81][82][83][84] In 2005, Sekine et al reported the supported synthesis of a diMe GppdT dimer (19) in which the 5 0 position of each nucleotide is connected by a pyrophosphate bridge (Fig. 11).…”
Section: Introductionmentioning
confidence: 99%
“…11). 83 The key step of the synthesis is the coupling of a supported 2 0 ,3 0 -boronoprotected activated guanine (20) with a thymidine monophosphate (21). After deprotection using 1% TFA in dichloromethane and cleavage from the support, dimer 19 was obtained in 49% isolated yield.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have been made to achieve selective deprotection of primary TBDMS ethers. Various acids including HCl, 5 HF, 6 acetic acid, 7,8 CSA, 9 toluenesulfonic acid (TsOH), 10 and trifluoroacetic acid (TFA) 11 have been investigated. Smith and Liu used 1% HCl in ethanol to selectively deprotect primary TBDMS ethers while performing the total synthesis of discodermolide.…”
mentioning
confidence: 99%